Intensitas Fungsi Modal Sosial untuk Penguatan Posisi Tawar Pengrajin dalam Pemasaran Souvenir Olahan Limbah Kelapa - . Dumasari; Sulistyani Budiningsih; Wayan Darmawan; Imam Santosa (Jurnal Ilmu Pertanian Indonesia, 2019)
A weak bargaining position in product marketing is a serious problem for farmers including those who diversify their livelihood patterns as souvenir craftsmen. Collector traders and retailers are dominant to set prices for souvenirs. Souvenir craftsmen surrender to accept any price level determination. As a consequence, souvenir craftsmen in the villages of Baturaden and Purbalingga Wetan have difficulties in earning profits from micro-souvenir businesses. The results of this study found that a solution to overcome the problem of the weak bargaining position of craftsmen in marketing souvenir products is through the use of a social-capital creation approach. The intensity of network functions of cooperation, mutual trust, values, and norms have different values in each bargaining position activity. Price domination by collectors and retailers is not only due to the dilemma of patron-client relationships. The qualities of souvenir products that are still not qualified turned out to be the cause of the weak bargaining position of craftsmen. The creation of social capital has a real function to strengthen the bargaining position of craftsmen in marketing souvenirs. The intensity of the function of social capital needs to be increased through the development of product quality, bargaining courage, and the ability to make price decisions in an agreement.